Network management activation in the implementation of policies to protect vulnerable groups from violence in Indonesia - Nur Islam, Firdha; Alwi, Alwi; Syahribulan, Syahribulan (Institute Of computer Science (IOCS), 2024)
This study aims to examine the role of network management activation in the implementation of child protection policies against violence in Makassar City. The research employs a qualitative approach, utilizing in-depth interviews with relevant stakeholders and document analysis to gather data. The results indicate that activation in network management is crucial for the effective implementation of child protection policies. Regional Regulation No. 5 of 2018 plays a significant role in providing legal protection for children, with the Women Empowerment and Child Protection Agency (DP3A) serving as the primary provider of child protection services. Collaboration with various parties, including the police, non-governmental organizations, and the community, is crucial in handling child violence cases. Complaints can be filed through formal and informal channels, with citizen shelters established to provide accessible protection services and eliminate social barriers to reporting violence. The study recommends that the Makassar City Government enhance coordination and communication among network actors, strengthen human resource capacity, optimize the allocated budget, intensify socialization of the Regional Regulation, and strengthen cooperation with non-governmental organizations and the community.